The Relative Power of the t-Test: A Comment - Tillman, J. A. (The Review of Economics and Statistics, 1974)
use of this distinction. And when we are confronted with terms of trade gains or losses between individual industries, caused by changes in relative prices that have been created artificially by protectionism, it would be most unfortunate to give it up. It does involve a lot of nasty index ambiguities, but that is a difficulty we have to live with, if at all we want to break down real national income changes in terms of trade gains, changes in primary factor quantities, and changes in productivity of primary factors. se of this distinctio . And when we are confronted REFERENCES